Toward a proposed framework for E-government readiness assessment. (1st December 2021) - Afshari-Mofrad, Masoud
E-government (EG) has become a necessity for governments in the information age and governors try to implement EG and assess its status to improve their services. Although many researchers studied EG implementation mostly in developed countries, there is still need for a comprehensive framework for EG implementation in developing countries. This study tried to review the literature and experiences of EG experts in a developing country in order to propose a framework which is fit with the needs of these countries. 92 questionnaires were completed by Iranian EG experts and analysing their responses using LMS technique and MPLUS 3.0 software validated the framework. Also, the framework was applied in Iran to investigate the status of EG readiness and the findings revealed that the country is experiencing an unbalanced trend in EG development. The findings showed that Iran's status in E-G is good in terms of human resources while policy making and soft infrastructures (soft) are the main weaknesses of the country.